Crisis intervention team training: when police encounter persons with mental illness. (3rd May 2020) - Bratina, Michele P.; Carrero, Kelly M.; Kim, Bitna; Merlo, Alida V.
Abstract: The Crisis Intervention Team (CIT) model is an established training program used to improve police response to encounters involving persons with mental illness (PwMI). Diversion of PwMI from the criminal justice system to appropriate treatment providers in the community is one of the primary goals of CIT. The present study examines characteristics and outcomes of encounters between citizens experiencing mental health-related crises and CIT-trained patrol officers. Findings of this study indicate encounters involving PwMI and CIT-trained officers often result in diversion to mental health services. Implications for policy and future research are discussed.